The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1029/2018pa003420
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Forcing, Ice Volume, and CO2 Across the Oligocene‐Miocene Transition

Abstract: Paleoclimate records suggest that a rapid major transient Antarctic glaciation occurred across the Oligocene‐Miocene transition (OMT; ca. 23 Ma; ~50‐m sea level equivalent in 200–300 kyr). Orbital forcing has long been cited as an important factor determining the timing of the OMT glacial event. A similar orbital configuration occurred 1.2 Myr prior to the OMT, however, and was not associated with a major climate event, suggesting that additional mechanisms play an important role in ice sheet growth and decay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 84 publications
(201 reference statements)
6
61
0
Order By: Relevance
“…2c) is independent of calibration error, based on universal gas-exchange mechanisms, and represents plant vegetative organs of multiple plant species that directly interacted with the available pool of atmospheric carbon dioxide. Previous Ca estimates from the Oligocene/Miocene boundary based on boron isotopes and paleosol carbonates are generally lower than our estimates (Ji et al, 2018;Greenop et al, 2019) (Fig. 4b), whereas Ca estimates based on stomatal index and recent alkenone-based Ca estimates are more similar to our results (Kürschner et al, 2008;Super et al, 2018).…”
Section: Earliest Miocene Co2supporting
confidence: 72%
See 2 more Smart Citations
“…2c) is independent of calibration error, based on universal gas-exchange mechanisms, and represents plant vegetative organs of multiple plant species that directly interacted with the available pool of atmospheric carbon dioxide. Previous Ca estimates from the Oligocene/Miocene boundary based on boron isotopes and paleosol carbonates are generally lower than our estimates (Ji et al, 2018;Greenop et al, 2019) (Fig. 4b), whereas Ca estimates based on stomatal index and recent alkenone-based Ca estimates are more similar to our results (Kürschner et al, 2008;Super et al, 2018).…”
Section: Earliest Miocene Co2supporting
confidence: 72%
“…The ESS envelope was determined using deep-sea δ 18 O of benthic foraminifera (Zachos et al, 2001) and the transform function approach from Hansen et al 2013(Supplementary Information). Proxy-based Neogene Ca reconstructions are derived from a previously published compilation (Foster et al, 2017) and are supplemented with more recently published data (Ji et al, 2019;Londoño et al, 2018;Super et al, 2018;Greenop et al, 2019;Moraweck et al, 2019, Steinthorsdottir et al, 2019. Error bars on gas-exchange based proxy estimates represent ±1σ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ the δ 11 B proxy on mixed-layer species of planktonic foraminifera in all core sites to first reconstruct surface ocean pH. The majority of Paleogene foraminiferal species selected for this study were previously identified to reflect surface mixed layer conditions 4,10 , and are likely characterized by a reduction in the degree of pH modification in the micro-environment surrounding the foraminifera by physiological processes compared to observations in modern foraminifera 4,14 . When thermocline dwelling species were used, or additional species not previously analysed, we ensured that our new analyses of δ 11 B overlapped with previously studied mixed-layer planktonic foraminiferal species ("Methods" and Supplementary Data 1) in order to constrain site-specific intra-species offsets and thus provide consistency and confidence in the derived mixed-layer pH (as in ref.…”
Section: Resultsmentioning
confidence: 99%
“…In the ~1 Myr prior to and following the O/M boundary (from 24.5 to 22 Ma)—an interval encompassing both warmer temperatures and lower average benthic δ 18 O than the preceding Oligocene—the larger amplitude (5°C) variation in midlatitude SST is coupled to a 1‰ range in benthic δ 18 O, with the warmest temperatures coinciding with minima in benthic δ 18 O. The Oligocene Miocene transitionitself is marked by a two‐step decrease in North Atlantic SST, analogous to the two‐step rise in high resolution benthic δ 18 O in orbitally resolved records (Liebrand et al, ; Mawbey & Lear, ), the pacing of which has been recently suggested to be driven by both changes in atmospheric carbon dioxide and obliquity (Greenop et al, ; Levy et al, ). Across the O/M boundary, previous high‐resolution analysis of a tropical Atlantic site between 22.4 to 23.7 Ma showed that intervals of increased δ 18 O sw interpreted as recording ice growth were coupled to intervals of bottom water cooling, inferred from benthic foraminiferal Mg/Ca (Mawbey & Lear, ).…”
Section: Discussionmentioning
confidence: 99%